Attitudes towards Lung Cancer Screening in an Australian High-Risk Population. (15th July 2013) - Flynn, Alexandra E.; Peters, Matthew J.; Morgan, Lucy C.
Abstract : Objectives . To determine whether persons at high risk of lung cancer would participate in lung cancer screening test if available in Australia and to elicit general attitudes towards cancer screening and factors that might affect participation in a screening program. Methods . We developed a 20-item written questionnaire, based on two published telephone interview scripts, addressing attitudes towards cancer screening, perceived risk of lung cancer, and willingness to be screened for lung cancer and to undertake surgery if lung cancer were detected. The questionnaire was given to 102 current and former smokers attending the respiratory clinic and pulmonary rehabilitation programmes. Results . We gained 90 eligible responses (M:F, 69:21). Mean [SD] age was 63[ 11 ] and smoking history was 32[ 21 ] pack years. 95% of subjects would participate in a lung cancer screening test, and 91% of these would consider surgery if lung cancer was detected. 44% of subjects considered that they were at risk of lung cancer. This was lower in ex-smokers than in current smokers. Conclusions . There is high willingness for lung cancer screening and surgical treatment. There is underrecognition of risk among ex-smokers. This misperception could be a barrier to a successful screening or case-finding programme in Australia.